2017
DOI: 10.1177/1045389x17730928
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorheological damper–based positioning system with power generation

Abstract: This study investigates a newly developed positioning system based on a rotary magnetorheological damper with power generation capability, comprising an electromagnetic power generator (energy extractor) generating electrical power, an magnetorheological damper which alters the damping characteristics of the system and an electrical interface, connected in between the coil of the generator and the damper control coil, which conditions the voltage output from the generator. Structural configurations of the damp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…For example, Jung et al 2010 studying a sensing capability of the harvester incorporated in the MR damper-based vibration control system showed that a harvester could well serve as a velocity sensor for common control methods in such systems. The present study recalls former works of the first author investigating energy harvesting MR dampers (Sapiński 2008, Sapiński 2014), exploring their applications in vibration reduction systems (Sapiński et al 2016) and in positioning systems (Sapiński et al 2018). The objective of the work is to demonstrate ability of the considered magnetic harvesters to act as velocity sensors.…”
Section: Introductionmentioning
confidence: 74%
“…For example, Jung et al 2010 studying a sensing capability of the harvester incorporated in the MR damper-based vibration control system showed that a harvester could well serve as a velocity sensor for common control methods in such systems. The present study recalls former works of the first author investigating energy harvesting MR dampers (Sapiński 2008, Sapiński 2014), exploring their applications in vibration reduction systems (Sapiński et al 2016) and in positioning systems (Sapiński et al 2018). The objective of the work is to demonstrate ability of the considered magnetic harvesters to act as velocity sensors.…”
Section: Introductionmentioning
confidence: 74%
“…The experiments were carried out with excitation z with an amplitude A = 3.5 mm and frequency f changed from 2 Hz to 10 Hz with a 0.1 Hz step. In each experiment lasting 20 s, three time intervals were distinguished: increasing the amplitude (0, 5) s, maintaining a constant amplitude (5, 15) s, and reducing the amplitude (15,20) s. The results of experiments performed at a constant amplitude of excitation z are shown in Figures 11 and 12. The plots in Figure 11 show the powers generated by the harvester P h , supplied to the MR damper control coil P d , and consumed by the ECU P el vs. frequency f. The power values P h , P d , and P el were calculated according to the Equations ( 3)- (5).…”
Section: Experimental Testing Of the Electrical Control Unit In The V...mentioning
confidence: 99%
“…The study [19] reports an H-bridge Graetz rectifier with a smoothing capacitor to convert AC current generated in a resonant electromagnetic vibration harvester into DC current supplying resistance load. The work [20] demonstrates a measurement and control unit with an H-bridge Graetz rectifier for conditioning the energy recovered from an object's oscillations in an MR rotary damper-based positioning system.…”
Section: Introductionmentioning
confidence: 99%
“…Tomori et al (2013) developed a one-degree-of-freedom manipulator using an artificial muscle and an MR brake to control the vibration and overshoot of the manipulator. Sapin´ski et al (2018) reported a magnetorheological damper-based positioning system. The overshoot and settling time of the system were reduced by the controlling of an MR damper.…”
Section: Introductionmentioning
confidence: 99%